Germinação e morfogênese in vitro de Dalbergia nigra (Vell.) Alemão ex Benth - Santos, Maricélia Moreira dos (2019)
The Atlantic Forest is a biome of great importance that suffers from human actions, which can lead to the extinction of endemic species of great economic and ecological value, such as the Brazilian rosewood (Dalbergia nigra (Vell.) Allemão ex Benth.). In order to aid in the multiplication of this remarkable species, this work aimed to study the in vitro germination and organogenesis of Dalbergia nigra using juvenile explants and phytoregulators, in order to contribute to the conservation of the species. For disinfestation and in vitro germination of Dalbergia nigra seeds, two experiments were carried out: 1. Different immersion times (0; 5; 10; 15; 20 and 25 minutes) in commercial sodium hypochlorite (NaOCl) (2.0-2.5% active chlorine), in a completely randomized design, where the NaOCl immersion times are the treatments, with four replicates of 25 seeds each, and 2. Different disinfectant agents, which were commercial NaOCl, hydrogen peroxide (H2O2), fungicide Captan SC and bactericidal Kasumin, performed in a completely randomized design, with seven treatments and four replicates of 10 seeds each. Woody Plant Medium - WPM was used in the germination and disinfestation experiments. For the analysis of NaOCl toxicity in Lactuca sativa L., it was used five concentrations of NaOCl (0.1, 0.5, 1.0, 1.5 and 2.0%), glyphosate solution (positive control) and distilled water (negative control), carried out in a completely randomized design, with five replicates of 25 seeds each. For in vitro cauligenesis of juvenile Dalbergia nigra explants, the seedlings grown in vitro were segmented into three explants of 1 cm each: caulinar apex, cotyledonary node and root. The explants were inserted in WPM medium supplemented with four concentrations of 6-benzylaminopurine (BAP) (0, 4.44, 8.88 and 13.32 µM), and were performed in a completely randomized design with a factorial 3x4 (explants x BAP), with four replicates of five explants per treatment. For in vitro rhizogenesis of Dalbergia nigra juvenile explants, cotyledonary node segments of normal in vitro grown seedlings were inserted into WPM culture medium with four concentrations of indole-3-butyric acid (IBA) (0, 4.92, 9.84 and 14.76 µM), being conducted in a completely randomized design, with four replicates of five explants per treatment. For greater disinfestation and less damaging effects to the seedlings, it is recommended that Brazilian rosewood seeds be treated with 70% alcohol for one minute and NaOCl for 15 minutes. The concentrations of BAP tested in juvenile explants were not satisfactory for cauligenesis. The concentration of 4.92 µM of IBA is recommended because it contributes to growth and root development without severely harming the development of shoots.